Mothering from the Inside Out: results of a pilot study testing a mentalization-based therapy for mothers enrolled in mental health services. Issue 6 (1st November 2016) - Suchman, Nancy E.; Ordway, Monica R.; de las Heras, Lourdes; McMahon, Thomas J.
ABSTRACT: Mothers who are involved with mental health services (for themselves or their children) rarely receive adequate support for their role as parents. Mental illness in a parent or child often exacerbates the challenges of managing psychological distress that is germane to the parenting roll. Mentalization-based approaches to psychotherapy for parents have the potential to address challenges of emotional regulation in parents by supporting their capacity to recognize and modulate negative affect during stressful parenting situations. In this study, we piloted Mothering from the Inside Out (MIO) with 17 mothers receiving services at a community-based mental health clinic. MIO is a 12-week, mentalization-based parenting intervention that demonstrated efficacy in two previous randomized controlled trials with substance using mothers. In this study, we were interested in determining whether community-based clinicians could deliver MIO with sustained fidelity. We were also interested in examining the preliminary feasibility, acceptability and efficacy of MIO when delivered by clinicians in a community mental health center. Finally, we were interested in replicating prior tests of the proposed treatment mechanisms. Treatment outcomes included maternal reflective functioning, psychiatric and parenting stress, and mother–child interaction quality. Our findings indicated that MIO was feasible and acceptable when delivered in the community-based setting and that all maternal indices improved. However, no improvement in mother–child interaction quality was found, possibly because of insufficient time for these changes to consolidate.